IITAs research for development agenda for Africa - Blade, S. (2008)
Agriculture is a primary driver for economic development in Africa. African agriculture must benefit from the research that can be conducted with the full arsenal of cutting-edge scientific tools to ensure food security, minimization of risk and the creation of wealth. The International Institute of Tropical Agriculture (IITA) is committed to assisting the African agricultural sector realize its potential through a research-for-development approach that ensures that innovative technologies reach the hands of users. IITA partners with advanced research institutions, national partners, the private sector and non-governmental organizations to keep improving technologies based on the suggestions and insight of users.